Medical evaluation of the surgical patient - Adler, Alan G (Saunders blue book series, 1985)
A highly useful guide to preoperative patient evaluation. This text defines the limits of the physician's responsibility, and describes the physician's role as advisor to the surgical team. Features a risk/benefit analysis of each major body system, helping to prevent oversights in evaluations and provide guidance in the timing of elective surgery. Also covers the perioperative phase.